Effects of Physical Activity on Mental Health and Cognitive Function: A Review of Current Evidence - Olubode, O. O.; Abdullah, Abdulsalam (NIU Journal of Social Sciences; Vol 11 No 3 (2025): NIU Journal of Social Sciences, Vol. 11 No. 3, September 2025, 2025)
The relationship between physical activity and mental health has attracted sustained scientific interest, with a rapidly expanding evidence base charting both the psychological benefits of regular exercise and the neurobiological mechanisms through which movement shapes brain structure and function. This narrative review synthesises peer-reviewed literature published between 2015 and 2026 examining the effects of physical activity on mental health outcomes — including depression, anxiety, stress, and subjective well-being — and on cognitive functions encompassing executive function, memory, attention, and processing speed across the lifespan. Six primary mechanistic domains are reviewed: monoaminergic and endocannabinoid neurochemistry, hypothalamic-pituitary-adrenal axis modulation, neuroplasticity and brain-derived neurotrophic factor upregulation, anti-inflammatory effects, psychosocial and self-efficacy pathways, and sleep-mediated mechanisms. Evidence from randomised controlled trials, longitudinal cohort studies, and meta-analyses consistently supports the conclusion that regular moderate-to-vigorous physical activity produces clinically meaningful improvements across mental health and cognitive outcome domains, with effect sizes comparable to those of pharmacological and psychological therapies for common mental disorders. Moderating variables including exercise intensity, modality, duration, social context, and individual characteristics are identified and their implications for exercise prescription discussed. Gaps in the evidence base — including a relative scarcity of long-term mechanistic studies, inadequate representation of older adults and LMICs, and limited investigation of dose-response thresholds — are highlighted alongside priorities for future research. Keywords: Physical activity, exercise, mental health, cognitive function, depression, anxiety, neuroplasticity, BDNF, executive function, well-being.